Anthropologie der Emotionen Affektive Dynamiken in Kultur und Gesellschaft - Stodulka, Thomas; von Poser, Anita; Scheidecker, Gabriel; Bens, Jonas (Reimer Verlag, 2023)
Emotions, feelings, affective dynamics: The anthropology of emotions has established itself as an interdisciplinary and transnational field of research. 27 authors from social and cultural anthropology, philosophy, psychology, sociology, the neurosciences and theatre studies outline the genesis and current developments of this research - in dialogue with Birgitt Röttger-Rössler's social and cultural-anthropological work and on the basis of the topics of perspectives, socialisation, mobility and politics. Thus, a new approach to the world of emotions emerges.